Clinical Response and Tolerability of Brivaracetam in Pediatric Epilepsy: A Systematic Review and Meta-analysis - Uneeb Ullah Khan; Mohammad Saboor Kamran; Muhammad Ansab; Ali Irtiza Talpur; Ayman Shakeel Ahmed; Ghadeer Mohammed Abbas; Syeda Zahra Hasan; Phan Huu Hung; Syed Hashim Ali Inam; Jabez David John; S.M Washaqul Arfin (Journal of Child Neurology, 2026)
This systematic review and meta-analysis aims to synthesize evidence on the safety and efficacy of brivaracetam (BRV) usage in pediatric epilepsy. The primary outcome of our study was to assess the endurability of BRV in a population of children (age ≤18 years) with epilepsy, which was measured by the retention rate. The responder rate, rate of seizure freedom, rate of adverse effects, and rate of withdrawal from the study were all taken as secondary outcomes, with a total number of 12 citations included in our meta-analysis. Pooled estimation gave us a retention rate of 66%, a responder rate of 35%, and a pooled seizure freedom rate of 13%. When analyzing adverse events data, 25% of patients experienced treatment emergent adverse events, whereas 9% experienced behavioral adverse events. This study reports that BRV is safe and effective in a pediatric population. These findings warrant the necessity for further studies in BRV effectiveness, with specificity toward different classifications of epilepsy, ideal dosages for beneficence, and larger trials.